The Dynamics of Sharia Compliance in Fintech Lending: Between Innovation and the Prohibition of Usury - Dzikri Maula Salam; Tabhita Prima Isnaeni; Baidhowi Baidhowi (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the dynamics of Sharia compliance in fintech lending within the context of digital financial innovation and the prohibition of usury. The research employs a non empirical normative legal approach based on the analysis of statutory regulations, Shari'ah standards, fatwas, and scholarly literature relevant to Islamic finance and fintech governance. The analytical framework integrates Islamic legal theory, Sharia compliance principles, and contemporary fintech governance to evaluate the compatibility of digital lending practices with Islamic commercial law. The findings indicate that Sharia fintech lending possesses a strong normative foundation through Qur'anic commercial principles, AAOIFI standards, national legislation, and Sharia regulatory instruments. Nevertheless, challenges remain in regulatory harmonization, governance effectiveness, compliance auditing, contractual standardization, and supervisory mechanisms. The study further identifies the growing relevance of technological innovations such as smart contracts, digital verification systems, open banking, and artificial intelligence based compliance monitoring in strengthening Sharia governance. Evaluated through the perspective of Maqasid al Shariah, these innovations can enhance transparency, accountability, consumer protection, and institutional sustainability. The study proposes an integrated governance model that balances technological advancement with substantive adherence to Islamic legal principles, thereby supporting the long term development of a credible and sustainable Sharia fintech ecosystem.